(untitled) (Journal of Pharmaceutical Negative Results, 2023)
Hantaviruses belong to the Bunyaviridae family as a separate genus. It is currently known that there are over 20 serogenotypes/ seroserotypes and that a number of new types are under investigation. The types of Hantaviruses which infect rodents tend to be specific to specific hosts and are primarily found in specific rodent species. As a result of the various types of Hantaviruses and their target organs, Hantaviruses can cause a variety of diseases. There are two major diseases in the world: hemorrhagic fever with renal syndrome (HFRS) and hemorrhagic fever with the syndrome (HPS). A new strain of Hantavirus has been observed in progressively increasing numbers within the world as a result of an accelerating increase in Hantavirus cases throughout the world, which represents an issue of public health of great concern across the globe. Hantavirus disease is a relatively new disease, however, its spectrum continues to expand as the number of recognized virus types continues to rise. It has been reported that Hantavirus causes human disease in the British Isles, but at this point, the disease is largely unknown. Hanta viral infection may be underestimated, especially in developing countries, due to its mild asymptomatic nature and lack of standardized laboratory diagnosis in hospitals. There are no simple standardized laboratory diagnoses in hospitals due to its asymptomatic and non-specific nature. Presented is an overview of what is currently known about hantaviruses and hantavirus infections, including their properties, classification, laboratory diagnostics, treatment, and prevention.